LEGAL REVIEW CONCERNING THE INDEPENDENCE OF JUDICIAL POWER: TINJAUAN HUKUM TENTANG INDEPENDENSI KEKUASAAN KEHAKIMAN - Maulana Sabani, maulana (UPMI Proceeding Series, 2023)
Judicial power is an independent body or institution and may not depend on other government agencies or institutions. The type of research in this paper is normative with a statutory and conceptual approach. The research specifications are analytical descriptive. The data used is secondary which consists of primary legal materials and secondary legal materials. The data analysis method was carried out qualitatively. The independence of the judicial power is an institutional position that must be free from political influence. The limits of the independence of the judiciary, legal provisions, religious accountability, namely accountability to God Almighty, the oath of office and the code of ethics for the honor of judges, accountability to society related to its decisions, fairness in justice according to one's conscience. For this reason, it is recommended that judges carry out their duties in accordance with the applicable laws and regulations.